Health Risks of Indoor Exposure to Particulate Matter: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The U.S. Environmental Protection Agency (EPA) defines PM as a mixture of extremely small particles and liquid droplets comprising a number of components, including "acids (such as nitrates and sulfates), organic chemicals, metals, soil or dust particles, and allergens (such as fragments of pollen and mold spores)". The health effects of outdoor exposure to particulate matter (PM) are the subject of both research attention and regulatory action. Although much less studied to date, indoor exposure to PM is gaining attention as a potential source of adverse health effects. Indoor PM can originate from outdoor particles and also from various indoor sources, including heating, cooking, and smoking. Levels of indoor PM have the potential to exceed outdoor PM levels.
Keywords: Health and Medicine

Achieving Behavioral Health Equity for Children, Families, and Communities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In November 2017, the The Forum on Promoting Children's Cognitive, Affective, and Behavioral Health, in collaboration with the Roundtable on the Promotion of Health Equity, convened a workshop on promoting children's behavioral health equity. The workshop used a socio-ecological developmental model to explore health equity of children and families, including those with complex needs and chronic conditions. Particular attention was paid to challenges experienced by children and families in both rural and urban contexts, to include but not limited to poverty, individual and institutional racism, low-resourced communities, and hindered access to educational and health care services. Workshop participants also engaged in solution-oriented discussions of initiatives, policies, and programs that aim to improve social determinants of health, opportunities for behavioral health promotion, and access to quality services that address the behavioral health of all children and families. This publication summarizes the presentations and discussion of the event.
Keywords: Health and Medicine; Behavioral and Social Sciences

Gulf War and Health: Volume 11: Generational Health Effects of Serving in the Gulf War - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
For the United States, the 1991 Persian Gulf War was a brief and successful military operation with few injuries and deaths. However, soon after returning from duty, a large number of veterans began reporting health problems they believed were associated with their service in the Gulf. At the request of Congress, the National Academies of Sciences, Engineering, and Medicine has been conducting an ongoing review of the evidence to determine veterans' long-term health problems and potential causes. Some of the health effects identified by past reports include post-traumatic stress disorders, other mental health disorders, Gulf War illness, respiratory effects, and self-reported sexual dysfunction. Veterans' concerns regarding the impacts of deployment-related exposures on their health have grown to include potential adverse effects on the health of their children and grandchildren. These concerns now increasingly involve female veterans, as more women join the military and are deployed to war zones and areas that pose potential hazards. Gulf War and Health: Volume 11 evaluates the scientific and medical literature on reproductive and developmental effects and health outcomes associated with Gulf War and Post-9/11 exposures, and designates research areas requiring further scientific study on potential health effects in the descendants of veterans of any era.
Keywords: Health and Medicine

Exploring Early Childhood Care and Education Levers to Improve Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On September 14, 2017, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the intersection of health and early childhood care and education, two key social determinants of health. This workshop follows a 2014 roundtable workshop that considered the interface between the education and health sectors broadly, from research and metrics to cross-sectoral partnerships and financing. The 2017 workshop continued that discussion, with a deeper focus on early childhood (birth through age 5) as a critical period in human development and an important opportunity for educational and related interventions. This publication summarizes the presentations and discussions from the 2017 workshop.
Keywords: Health and Medicine

Environmental Chemicals, the Human Microbiome, and Health Risk: A Research Strategy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
A great number of diverse microorganisms inhabit the human body and are collectively referred to as the human microbiome. Until recently, the role of the human microbiome in maintaining human health was not fully appreciated. Today, however, research is beginning to elucidate associations between perturbations in the human microbiome and human disease and the factors that might be responsible for the perturbations. Studies have indicated that the human microbiome could be affected by environmental chemicals or could modulate exposure to environmental chemicals.
Keywords: Environment and Environmental Studies

The Convergence of Infectious Diseases and Noncommunicable Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On June 11 and June 12, 2019, the National Academies convened a workshop to explore the growing understanding of how the interplay between humans and microbes affects host physiology and causes noncommunicable diseases. Discussions included an overview of colliding epidemics, emerging research on associations between infectious and noncommunicable diseases, risks posed by chronic diseases to the development and severity of infectious diseases, and the influence of the microbiome. Workshop participants also examined the challenges and opportunities of convergence, the integration of health care delivery models and interventions, potential approaches for research, policy, and practice in the immediate-term, and potential directions for the long-term. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Using 21st Century Science to Improve Risk-Related Evaluations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Over the last decade, several large-scale United States and international programs have been initiated to incorporate advances in molecular and cellular biology, -omics technologies, analytical methods, bioinformatics, and computational tools and methods into the field of toxicology. Similar efforts are being pursued in the field of exposure science with the goals of obtaining more accurate and complete exposure data on individuals and populations for thousands of chemicals over the lifespan; predicting exposures from use data and chemical-property information; and translating exposures between test systems and humans. Using 21st Century Science to Improve Risk-Related Evaluations makes recommendations for integrating new scientific approaches into risk-based evaluations. This study considers the scientific advances that have occurred following the publication of the NRC reports Toxicity Testing in the 21st Century: A Vision and a Strategy and Exposure Science in the 21st Century: A Vision and a Strategy. Given the various ongoing lines of investigation and new data streams that have emerged, this publication proposes how best to integrate and use the emerging results in evaluating chemical risk. Using 21st Century Science to Improve Risk-Related Evaluations considers whether a new paradigm is needed for data validation, how to integrate the divergent data streams, how uncertainty might need to be characterized, and how best to communicate the new approaches so that they are understandable to various stakeholders.
Keywords: Environment and Environmental Studies

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere.
Keywords: Earth Sciences

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Children are the foundation of the United States, and supporting them is a key component of building a successful future. However, millions of children face health inequities that compromise their development, well-being, and long-term outcomes, despite substantial scientific evidence about how those adversities contribute to poor health. Advancements in neurobiological and socio-behavioral science show that critical biological systems develop in the prenatal through early childhood periods, and neurobiological development is extremely responsive to environmental influences during these stages. Consequently, social, economic, cultural, and environmental factors significantly affect a child's health ecosystem and ability to thrive throughout adulthood. Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity builds upon and updates research from Communities in Action: Pathways to Health Equity (2017) and From Neurons to Neighborhoods: The Science of Early Childhood Development (2000). This report provides a brief overview of stressors that affect childhood development and health, a framework for applying current brain and development science to the real world, a roadmap for implementing tailored interventions, and recommendations about improving systems to better align with our understanding of the significant impact of health equity.
Keywords: Health and Medicine; Education

Microbiomes of the Built Environment: A Research Agenda for Indoor Microbiology, Human Health, and Buildings - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
People's desire to understand the environments in which they live is a natural one. People spend most of their time in spaces and structures designed, built, and managed by humans, and it is estimated that people in developed countries now spend 90 percent of their lives indoors. As people move from homes to workplaces, traveling in cars and on transit systems, microorganisms are continually with and around them. The human-associated microbes that are shed, along with the human behaviors that affect their transport and removal, make significant contributions to the diversity of the indoor microbiome.
Keywords: Biology and Life Sciences; Engineering and Technology

Principles and Obstacles for Sharing Data from Environmental Health Research: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 19, 2014, the National Academies of Sciences, Engineering, and Medicine held a workshop on the topic of the sharing of data from environmental health research. Experts in the field of environmental health agree that there are benefits to sharing research data, but questions remain regarding how to effectively make these data available. The sharing of data derived from human subjects—making them both transparent and accessible to others—raises a host of ethical, scientific, and process questions that are not always present in other areas of science, such as physics, geology, or chemistry. The workshop participants explored key concerns, principles, and obstacles to the responsible sharing of data used in support of environmental health research and policy making while focusing on protecting the privacy of human subjects and addressing the concerns of the research community. Principles and Obstacles for Sharing Data from Environmental Health Research summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Veterans and Agent Orange: Update 11 (2018) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
From 1962 to 1971, the U.S. military sprayed herbicides over Vietnam to strip the thick jungle canopy that could conceal opposition forces, to destroy crops that those forces might depend on, and to clear tall grasses and bushes from the perimeters of US base camps and outlying fire-support bases. Mixtures of 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), picloram, and cacodylic acid made up the bulk of the herbicides sprayed. The main chemical mixture sprayed was Agent Orange, a 50:50 mixture of 2,4-D and 2,4,5-T. At the time of the spraying, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic form of dioxin, was an unintended contaminant generated during the production of 2,4,5-T and so was present in Agent Orange and some other formulations sprayed in Vietnam. Because of complaints from returning Vietnam veterans about their own health and that of their children combined with emerging toxicologic evidence of adverse effects of phenoxy herbicides and TCDD, the National Academies of Sciences, Engineering, and Medicine was asked to perform a comprehensive evaluation of scientific and medical information regarding the health effects of exposure to Agent Orange, other herbicides used in Vietnam, and the various components of those herbicides, including TCDD. Updated evaluations were conducted every two years to review newly available literature and draw conclusions from the overall evidence. Veterans and Agent Orange: Update 11 (2018) examines peer-reviewed scientific reports concerning associations between various health outcomes and exposure to TCDD and other chemicals in the herbicides used in Vietnam that were published between September 30, 2014, and December 31, 2017, and integrates this information with the previously established evidence database.
Keywords: Health and Medicine